Advances in Controlling Differentiation of Adult Stem Cells for Peripheral Nerve Regeneration. Issue 14 (14th April 2018) - Uz, Metin; Das, Suprem R.; Ding, Shaowei; Sakaguchi, Donald S.; Claussen, Jonathan C.; Mallapragada, Surya K.
Abstract: Adult stems cells, possessing the ability to grow, migrate, proliferate, and transdifferentiate into various specific phenotypes, constitute a great asset for peripheral nerve regeneration. Adult stem cells' ability to undergo transdifferentiation is sensitive to various cell‐to‐cell interactions and external stimuli involving interactions with physical, mechanical, and chemical cues within their microenvironment. Various studies have employed different techniques for transdifferentiating adult stem cells from distinct sources into specific lineages (e.g., glial cells and neurons). These techniques include chemical and/or electrical induction as well as cell‐to‐cell interactions via co‐culture along with the use of various 3D conduit/scaffold designs. Such scaffolds consist of unique materials that possess controllable physical/mechanical properties mimicking cells' natural extracellular matrix. However, current limitations regarding non‐scalable transdifferentiation protocols, fate commitment of transdifferentiated stem cells, and conduit/scaffold design have required new strategies for effective stem cells transdifferentiation and implantation. In this progress report, a comprehensive review of recent advances in the transdifferentiation of adult stem cells via different approaches along with multifunctional conduit/scaffolds designs is presented for peripheral nerve regeneration. Potential cellular mechanisms and signaling pathways associated with differentiation are also included. The discussion with current challenges in the field and an outlook toward future research directions is concluded. Abstract : The use of adult stem cells holds considerable potential for nerve regeneration applications due to their ability to differentiate into specific cell lineages. This progress report particularly focuses on the recent advances in adult stem cell differentiation strategies including scaffold/conduit materials and electrical/chemical stimulation methods for peripheral nerve regeneration.